FRAMING MAKNA JIHAD DALAM AL-QURAN PERSPEKTIF TAFSIR MAQASIDI - Suaib Tahir, Muhammad (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2023)
Jihad in an Islamic perspective has many meanings, including fighting in the way of Allah (fis sabilillah). The Qur'an as a guide for Muslims explains several things related to jihad. In this article, there are three discussions about the aims and objectives behind the implicit and unspoken texts of the verses about jihad. First aim is to upholding Allah's religion. Second aim is to protect Muslims in Mecca from destruction and loss. This aim is motivated by several considerations which are the background revelation QS. An Nisa'/4: 77. Third aim is to protect the dignity of the Muslim community and maintain their existence. This goal is the background for revelation Q.S. Al-Taubah/9: 73. This research is library research by studying and examining the verses about jihad in the Qur’an which means war, then interpreting these verses using “tafsir maqasidi” application. It is hoped that this article will become one of the treasures of “tafsir maqasidi”. Apart from that, it is also hoped that this article will be able to provide insight for Muslims, especially in the Indonesian context regarding the beneficial objectives behind the jihad verses in the Qur’an